2013
DOI: 10.12968/bjom.2013.21.6.394
|View full text |Cite
|
Sign up to set email alerts
|

Electronic fetal monitoring during labour and anxiety levels in women taking part in a RCT

Abstract: The INFANT study is a randomised controlled trial to determine whether decision-support software for electronic fetal monitoring can reduce the number of babies born with poor outcomes compared to electronic fetal monitoring alone. A mixed methods sub-study was undertaken as part of INFANT to examine the effects of the technologies being used on the anxiety levels of those women randomised: 469 women were asked to measure their anxiety levels using a Visual analogue scale–anxiety (Vas-a) at three time points (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Pregnancy is an anxious time for some women, even during a normal antenatal period and labour, in part generated by fears and uncertainty about the outcome [ 39 ]. Studies of women’s anxiety levels during labour and how they are affected by additional fetal monitoring [ 40 ] have shown that women can be reassured by active monitoring. Although the very use of fetal monitoring can imply birth is a risky process needing careful monitoring, women appeared reassured.…”
Section: Discussionmentioning
confidence: 99%
“…Pregnancy is an anxious time for some women, even during a normal antenatal period and labour, in part generated by fears and uncertainty about the outcome [ 39 ]. Studies of women’s anxiety levels during labour and how they are affected by additional fetal monitoring [ 40 ] have shown that women can be reassured by active monitoring. Although the very use of fetal monitoring can imply birth is a risky process needing careful monitoring, women appeared reassured.…”
Section: Discussionmentioning
confidence: 99%
“…The cord of the machine was lying in the water ” 26 (p351) ; “[I was] worried the whole time that the baby's heart would stop if the machine stopped .” 27 (p2112) Furthermore, labouring women experienced the CTG as a barrier to effective and personal communication; “ They all came with the machine and left with the machine, ” 27 (p2112) “ Everyone was just focused on this monitor and the heartbeat…. it was making me panic .” 28 (p401) These narratives place emphasis on a lack of SDM associated with the use of EFM. For example, the evidence from Alfirevic's review shows that CS increases with the use of EFM compared to less technological methods of monitoring the fetal heart rate, 22 yet women are rarely informed of this in practice; they may not know how the technology works or the reason for its application in the first place—yet may accept this technological intervention on the basis of common practice, and a “doctor knows best” mentality, despite their fear and anxiety.…”
Section: The Case Of Electronic Fetal Monitoring In Maternity Carementioning
confidence: 99%
“…Analyses of the data have been published in peer-reviewed journals over the past 10 years. [16][17][18][19][20][21] Illustrated lay summaries of the research findings are also disseminated via a website, owned by the DIPEx (Database of Individual Patient Experiences) charity: www.healthtalkonline.org. The website has NHS Information Standard approval and the collections are reviewed every 2 years and updated with further interviews if considered necessary, for example to capture the experiences of people who have used new treatments or therapies.…”
Section: Quality Standardsmentioning
confidence: 99%